Evidence of Ehrlichia chaffeensis in Argentina through molecular detection in marsh deer (Blastocerus dichotomus) - Guillemi, Eliana Carolina (2019)
Vector-borne pathogens are responsible for serious emerging diseases and have been widely described in wildlife. Ehrlichia chaffeensis causes the zoonotic “monocytic ehrlichiosis” in humans, is transmitted by the tick Amblyomma americanum and its reservoir host is the white-tailed deer (Odocoileus virginianus) in North America. Little is known about the native reservoir and the tick vectors involved in the transmission cycle in South America. We report here the detection of E. chaffeensis in a study on marsh deer (Blastocerus dichotomus) mortality in Argentina, in different time periods between 2007 and 2016. Four deer, from two distinct populations, were positive for E. chaffeensis through molecular methods. Additionally, the variable-length PCR target (VLPT) region of positive samples was genotyped. Our results provide the first evidence of E. chaffeensis in autochthonous Cervidae from Argentina, contributing to uncover the distribution of this tick-borne infection in South America.